Mundialization, social work and subject’s policy - Biarnès, Jean (Acolhendo a Alfabetização nos Países de Língua Portuguesa, 2008)
The article presents some possibilities for a subject´s policy envolving question of ethics and democracy. It is based on the analysis of a work realized by two groups of the EQUAL Program. These groups accompany the social insertion of young people in France. According to the author, they should evaluate their social work taking into account, at the same time, the quantitative dimension and the qualitative dimension in relation to the person as subject. This way, it comes to sight an urgent consequence that social actors get worry about constructing their own evaluators instruments of their work, in order to a qualitative and no quantitative evaluate, respecting a real subject´s dynamic, from the user side as well from the social actor side in which each one has the necessity of unveiling (reciprocal "biographization"), explicating their criterions according to their point of view about common lived situations (re-"territorialization" of the person) and trying to permanence coherent ("desparcialization" of the person inside different trajectories). All these work ought to take into account that "being subject" can not ever be isolated from the object. The "being subject" is a "being in situation". "Being subject" is to be a "subject who talks and acts", it means, a "subject who desires", in a social scenario in which world-wide dominance is delimited by imprecisely borders inside their concretizations and an extreme efficacy inside their functioning. In this context, to educate - to form, to accompany the dimension of subject´s creative desire - is the first mission that should be given to all social worker, by himself and by his work with the Other. This knowledge of the subject and his own word implicates that social actor "works with" instead of "works for" the subject.